ANALISIS TINGKAT KEPUASAN TERHADAP KUALITAS LAYANANPENDIDIKAN DENGAN METODE SERVICE QUALITY DAN IMPORTANCE PERFORMANCE ANALYSIS DI SMK NEGERI 1 PALABUHANRATU - Rio Rokhmani (Mimbar Administrasi Mandiri, 2022)
Students are direct users of the education service system, so schools must provide satisfaction and positive trust to students so that they believe that they are in a place that is suitable for developing their potential to be ready to face competition in society. The purpose of this study was to determine the quality of education services at SMKN 1 Palabuhanratu and to find out what indicators need to be improved by SMKN 1 Palabuhanratu in order to improve service quality. This research method uses quantitative descriptive with Proportionate Stratified Random Sampling. The results showed that simultaneously the level of satisfaction of students at SMKN 1 Palabuhanratu with their education services was "Quite Satisfied" or 53.18%. Furthermore, the performance indicators that must be improved by schools to improve services and the very high expectations of students towards their education are in the attributes (1) Teachers provide examples to their students about good education, (2) The education system implemented in this school is in accordance with developments. era, (3) Supervision of the learning process in this school is good, (4) The knowledge obtained by students at this school is in accordance with the expectations of students and their parents and (5) The skills obtained by students in this school are in accordance with the expectations of students and their parents